Assessing the validity of admission test into the internship programme at a private university in Pakistan - Qamar Riaz; Yousuf, Naveed; Shamim, Muhammad Shahzad (Journal of the Pakistan Medical Association, 2022)
Objective: To report the development and validity assessment of a comprehensive model of assessment method comprising written test and multiple mini interviews for selection in a medical internship programme. Method: The psychometric validation study was conducted at the Aga Khan University, Karachi, and comprised anonymised scores of written admission test, multiple mini interviews and exit written exams for all the interns who completed their internships in 2018 and 2019. Correlation between admission and exit tests, and predictions were assessed. Data was analysed using SPSS 20. Results: There were 160 interns; 80(50%) each in 2018 and 2019. Mean scores were 68.8+4.40% for written tests and 76.7+4.66% for multiple mini interviews. The mean score for exit examination was 68.1+6.84%. The Cronbach’s alpha of scores on the written admission test was 0.82 and 0.88 for the two years, respectively, while for the multiple mini interviews, the corresponding values were 0.81 and 0.94. The written admission and exit tests were moderately correlated (0.44) while the correlations of multiple mini interviews scores with written admissions and exit tests were -0.28 and 0.04, respectively. Conclusion: The selection process should comprise multiple measures of assessment to ensure the selection of the best candidates. Key Words: Multiple mini interviews, Predictive validity, Admission test.